ANALYSIS OF BIOPHARMACY CROPS PRODUCTION AND EXPORTS ON AGRICULTURAL SECTOR GDP GROWTH RATE (2012-2022) - Shahrul, Shahrul (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
The objectives of this study are to: 1) determine the number of developments in biopharmaceutical production, 2) determine the number of biopharmaceutical plant exports, and 3) determine the impact of biopharmaceutical plant production and exports on the agricultural sector's GDP growth rate from 2012 to 2022. This type of research employs quantitative panel data. Data on biopharmaceutical crop output, exports, and national income from 2012 to 2022 were obtained from the Central Statistics Agency (BPS) and other sources. The data analysis technique employs correlation analysis and the F test. The study's findings demonstrate that: 1) biopharmaceutical plant production and export have a substantial impact on agricultural economic growth. 2) There is a positive association between biopharmaceutical crop production and exports and agricultural GDP growth, although this trend can be altered by a variety of external and internal factors. 3) This research, however, demonstrates that various fluctuations and issues must be addressed in order to secure the agricultural sector's long-term and equitable growth. Keywords:biopharmaceuticals, exports, production, growth rate